Anti-inflammatory effect of apigenin and hydroalcoholic extract of Dracocephalum kotschyi on acetic acid-induced colitis in rats - Hassan Sadraei (Research in Pharmaceutical Sciences, 2017)
Colitis is an inflammatory disease of the intestine with unknown etiology involving multiple immune, genetic, and environmental factors. We were interested to examine the effect of total extract from Dracocephalum Kotschyi (D. kotschyi) Boiss. on the experimental colitis. D. kotschyi hydroalcoholic extract (10, 20, and 40 mg/kg) or apigenin (5, 10, and 20 mg/kg) were administered orally 2 h prior to induction of colitis which was induced by intrarectal administration of acetic acid (4%) in rats. Prednisolone (4 m/kg) was used as the standard drug for comparison. Biochemical evaluation of inflamed colon was performed by measuring myeloperoxidase (MPO) activity. After 5 days treatment, mucosal ulceration was evaluated. Intrarectal instillation of acetic acid caused significant inflammatory reactions as indicated by macroscopic and microscopic changes. The activity of MPO increased in vehicle treated groups while recovered to normal level by pretreatment of animals with D. kotschyi extract, apigenin, or prednisolone. D. kotschyi and apigenin-treated groups showed significantly lower score values of macroscopic and microscopic characters when compared with the vehicle-treated negative control group. The beneficial effect of apigenin was comparable with that of prednisolone. This research has shown the anti-inflammatory potential of D. kotschyi extract and apigenin in experimentally induced colitis.